Semantik Verba dalam Membentuk Gaya Bahasa pada Judul Berita Tempodotco - Agustina, Hani; Mahyuni, Mahyuni; Burhanuddin, Burhanuddin (Universitas Hamzanwadi, 2022)
The headline is the main highlight that readers see in a news story. Tempodotco digitized its printed news headlines. The digitization of this news title is done by visualizing it in the form of a poster. The purpose of this study is to describe the semantic behavior of groups of basic verbs, derivative verbs, and verbal phrases in forming metaphors and personifications in news titles on the Tempodotco digital media Instagram page. This research method uses descriptive method. The data collection method is the method of listening and documentation. The type of data in this research is qualitative data in the form of pictures and words in the news title. Data analysis used the Miles and Huberman model which includes data analysis, data reduction, data display, and data verification. In this study, it was found that 1) the basic verb group has three inherent meanings of action or action and one inherent meaning of state. The language style formed is three metaphors and one personification. 2) The semantic behavior of the derived verb group which is transitive has five inherent meanings, one action inherent meaning, and one process inherent meaning. The language style formed is three metaphors and two personifications. 3) The semantic behavior of the verbal phrase group has all the inherent meanings of the action and forms three metaphors and one personification. In this study, there is no reduplication of the verb.Keywords: Title, Verb, Semantics, Metaphor, Personification, Phrase